Akuntansi Pencatatan Pembukaan dan Pencairan Deposito Berjangka pada PT. BPR Anugerahdharma Yuwana Cabang Ambulu Kabupaten Jember - Riswandari, Ira Mei; Suwarso, Suwarso; Tohari, Nursyamsida (Program Studi Akuntansi Fakultas Ekonomi Universitas PGRI Argopuro Jember, 2023)
The purpose of this research is to determine the recording of opening and disbursement of time deposits at PT. BPR Anugerahdharma Yuwana Ambulu Branch, Jember Regency and compare it with theory. The research method used is descriptive qualitative with data collection techniques of interviews, observation, and documentation. The results of this study are the recording of the opening and disbursement of time deposits at PT. BPR Anugerahdharma Yuwana Ambulu Branch, Jember Regency uses the Cash Basis system, and the recording is also in accordance with the theory, except that there is a slight difference in the recording of account names and deposit interest taxes are not included in the interest payment journal in accordance with company policy.